Tinyville Town - Time for school! - Biggs, Brian (Abrams Appleseed, 2017)
Even though she has just moved to Tinyville Town, everyone at her new school, from Principal Paul to the lunch lady, is kind and does his or her part to keep things running smoothly for Ellie Emberley on her first day of school
Keywords: Einschulung; Freundschaft; First day of school / Juvenile fiction; Schools / Juvenile fiction; Friendship / Juvenile fiction; First day of school / Fiction; Schools / Fiction; JUVENILE FICTION / People & Places; JUVENILE FICTION / School & Education; JUVENILE FICTION / Social Themes / New Experience; Friendship; First day of school; Schools; JUVENILE FICTION / People & Places / General; Fiction; Juvenile works; Bilderbuch